Characterization, conservation and utilization of indigenous African animal genetic resources - ILCA's proposed program - Rege, J.E.O.; Baker, R.L. (International Laboratory for Research on Animal Diseases, 1994)
Sub-Saharan Africa is rich in animal biodiversity. Over 95 percent of the continent's domestic ruminants are indigenous. In Africa, indigenous livestock breeds support the majority of smallholder rural farmers for whom these genetic resources are important for improved nutrition, income and as investment. However, relatively little is known about Africa's indigenous livestock resources, even in terms of how many breeds there are and the degree to which useful genetic adaptation to disease, parasite and nutritional stress have evolved. The objectives of ILCA's proposed program are to characterize indigenous African livestock breeds, to formulate action plans that might arrest or reverse declines in threatened or endangered population, to develop strategies for conservation and sustainable utilization of indigenous gentic resources, including utilization of economically important unique attributes, to adapt techniques in collection, evaluation and storage of gametes and embryos for ex situ preservation of endangered breeds, and to develop a computerized database on African animal genitic resources in line with recommendations by FAO / UNEP and OAU.